HUBUNGAN KEPEMIMPINAN PROFETIK KEPALA SEKOLAH DENGAN PRODUKTIVITAS KERJA TENAGA PENDIDIK - Fadlan Hafiz; Nifasri Nifasri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the importance of the principal's leadership role in increasing the work productivity of educators. Effective leadership, especially prophetic leadership, is believed to be able to create a conducive work environment and improve teacher performance. This study aims to determine the application of prophetic leadership by the principal, the level of work productivity of educators, and the relationship between prophetic leadership and work productivity of educators at SMAN 11 Bandung City. This study uses a quantitative approach with a correlational method. The sample in this study amounted to 68 educators. The data collection technique used a questionnaire, while data analysis used validity, reliability, normality, correlation, and regression tests with the help of the SPSS application. The results showed that the principal's prophetic leadership was in the high category with an average value of 3.99. The work productivity of educators was also in the high category with an average value of 4.05. In addition, there was a positive and significant relationship between prophetic leadership and work productivity of educators with a significance value of 0.001 <0.05 and a correlation coefficient of 0.485 which was in the medium category. Thus, it can be concluded that the principal's prophetic leadership has a positive and significant relationship with the work productivity of teaching staff at SMAN 11 Bandung City. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya peran kepemimpinan kepala sekolah dalam meningkatkan produktivitas kerja pendidik. Kepemimpinan yang efektif, khususnya kepemimpinan profetik, diyakini mampu menciptakan lingkungan kerja yang kondusif dan meningkatkan kinerja guru. Penelitian ini bertujuan untuk mengetahui penerapan kepemimpinan profetik oleh kepala sekolah, tingkat produktivitas kerja pendidik, serta hubungan antara kepemimpinan profetik dengan produktivitas kerja pendidik di SMAN 11 Kota Bandung. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Sampel dalam penelitian ini berjumlah 68 pendidik. Teknik pengumpulan data menggunakan angket, sedangkan analisis data menggunakan uji validitas, reliabilitas, uji normalitas, korelasi, dan regresi dengan bantuan aplikasi SPSS. Hasil penelitian menunjukkan bahwa kepemimpinan profetik kepala sekolah berada pada kategori tinggi dengan nilai rata-rata sebesar 3,99. Produktivitas kerja pendidik juga berada pada kategori tinggi dengan nilai rata-rata sebesar 4,05. Selain itu, terdapat hubungan yang positif dan signifikan antara kepemimpinan profetik dengan produktivitas kerja pendidik dengan nilai signifikansi sebesar 0,001 < 0,05 dan koefisien korelasi sebesar 0,485 yang berada pada kategori sedang. Dapat disimpulkan bahwa kepemimpinan profetik kepala sekolah memiliki hubungan positif dan signifikan terhadap produktivitas kerja pendidik di SMAN 11 Kota Bandung.